Accounting students perception on pursuing professional exam. - Mustapha, Mazlina; Abu Hassan , Mohammad Hasmawi
Prior studies indicate that people’s perception have an important influence on their career decisions. This study explores the accounting students’ perceptions on professional examination and the factors that influence their decisions to take the exam. Questionnaires were distributed to final year accounting students of a public university in Malaysia. About 103 questionnaires were completed and usable for the purpose of the study. Regression analysis was employed to analyse the data. The results indicate that about 70% of the respondents plan to work immediately after graduating, and only about 28% of the respondents really have the intention to pursue professional qualification. Among others, the findings reveal that the job security and stability, and opportunities for advancement as well as the students’ perception towards the profession are the three main variables found to be significant in influencing the accounting students’ decision to pursue professional examination. The results of the study appear to suggest that the educators and universities must play their role to positively influence and motivate the students to pursue professional examination. The favourable information about the profession may attract the potential students to take the challenge.